(untitled) (International Journal of Economics Management and Social Science, 2025)
This narrative review examines “green employee behavior” the actions by employees that support environmental sustainability in Indonesian companies, focusing on the mining sector and recent (2024–2025) open-access research. We evaluate whether Ajzen’s Theory of Planned Behavior (TPB, Ajzen, 1991) applies to this context. First, key concepts are defined: green employee behavior (EGB) and TPB. Next, the core constructs of TPB (attitude, subjective norm, and perceived behavioral control) are described in an environmental-management context. We then synthesize evidence from Indonesian studies (emphasizing mining) to assess TPB’s explanatory power. Indonesian research indicates that attitudes toward sustainability, social/group norms, and employees’ confidence in their ability to act (PBC) significantly influence green behaviors. In coal mining and tourism firms, green HRM practices, training, and leadership support have been shown to enhance these TPB factors, thereby promoting EGB. For example, observing colleagues engage in green practices establishes social norms that encourage similar behavior. Overall, the literature suggests that TPB is largely applicable: its constructs appear relevant in Indonesian workplaces. However, several studies also integrate additional factors (e.g. organizational culture, values, and leadership) alongside TPB to capture the complex drivers of EGB. We conclude that TPB provides a useful framework for understanding green employee behavior in Indonesia, especially when extended with context-specific variables. Implications for theory and practice in sustainable management are discussed.